Utilization Status of Improved Garri Processing Technology in South Eastern Nigeria - K C Ekwe; I Nwachukwu (Journal of Agricultural Extension, 2006)
The improved garriprocessing technology collaboratively developed by International Institute Tropical Agriculture (Ibadan), andNational Root Crops Research Institute Umudike has been withfarmers South eastern Nigeriafor over two decades. This paper seeks to investigate the status of utilization of this technology which appears to be popular among farmers Nigeria. Thrionugh structured questionnaires, data were collected from 320 farmers randomly sampled from five out nine states that consotiftute the South east agro ecological zone. Data were analyzed with descriptive and Product-moment co-relation statistics. Analysis ofdata collected showed that the technology was in the medium level inofthuetilsiztuadtiyoanrea withmost farmers using two out offivepractices in the technology. Again, while majority offarmers utilized the grating machine (79.37%) and de-watering press (65.31%), less than halfof the farmers utilized the recommendedfermentationperiod(39.38%) whilefew utilized garri sieving machine (15.62%) and garrifrying tray (12.81%). Also a strong relationship existed between grating machine and de-watering press as well as between sieving machine and garrifrying tray. It was thus recommended that efforts should be made by extension agencies in the zone to promote andpopularize the advantage of processing technology over the traditional method as well as sensitize thefarmers on the dangers of inadequatefermentation ofgarri. Also Governments and nonÂ¬governmental organisations canfacilitate the adoption of the improved garriprocessing technology by establishing of prototypeprocessing centresforfarmers co-operative societies in the,rural areas. This will encouragefarmers to utilize the technology as recommended.